Constructing anatomical terminology in Middle English: the case of British Library, MS Sloane 3486 (? . 140v–147v) - Domínguez Rodríguez, María Victoria (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen